KONTRIBUSI KECEPATAN TENDANGAN, KEKUATAN OTOT TUNGKAI, KOORDINASI MATA DAN TANGAN TERHADAP SERANGAN ATLET PENCAK SILAT TAPAK SUCI SUMEDANG - Willy Fitra Mahardika (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
This research aims to 1) find out the effect of kick speed on the combination of attacks pencak silat sacred site Sumedang.; 2) knowing the impact of the strength of the limb muscles against the combination of attacks of Pencak Silat Sacred Site Sumedang; 3) know the influence exerted by the speed of kicks through eye and hand coordination against the combination of attacks of Pencak Silat Sacred Site Sumedang; 4) knowing the influence exerted by muscle strength through eye and hand coordination against the combination of attacks of Pencak Silat Sacred Site Sumedang; 5) know the influence exerted by kicking and leg muscle strength through eye and hand coordination against the combination of attacks pencak silat sacred site Sumedang.The research method used is quantitative research with an associative correlation approach. This research belongs to a type of quantitative research that uses Path Anaylisis techniques. The sample in this study was pencak Silat Young Athletes pencak Silat Holy Site Sumedang which numbered 64 people. The data taken in this study used primary and secondary data. Primary data is data obtained or taken directly by researchers through tests and measurements of variables contained in the study. Secondary data, is data obtained in the form of a list of athletes' names obtained from documents or archives. The data analysis technique used is to use Path analysis or path analysis. The results of the study found (1) There was a significant direct influence of kick speed on the coordination of punches and kicks pencak Silat Athletes Sacred Site Sumedang indicated with a coefficient r of 0.681, and the significance of the relationship of variable X1 with variable Y can be seen the value of t calculated by 2,113 > with t table of 1,701. The results of the study found (1) There was a significant direct influence of kick speed on the coordination of punches and kicks pencak Silat Athletes Sacred Site Sumedang indicated with a coefficient r of 0.681, and the significance of the relationship of variable X1 with variable Y can be seen the value of t calculated by 2,113 > with t table of 1,701. The direct influence of the strength of the limb muscles on the coordination of punches and kicks of Pencak Silat Athletes of The Sacred Site of Sumedang is 42.40%. (3) There is a significant direct influence of eye coordination on the coordination of punches and kicks of Pencak Silat Athletes of The Holy Site of Sumedang indicated by a coefficient of r of 0.664, and the significance of the relationship of variable X3 with variable Y can be seen the value of t calculated by 1.997 > with t table of 1.701. The large influence of eye coordination on the coordination of punches and kicks of Pencak Silat Athletes of The Sacred Site of Sumedang is 54.70%.